LOKAKARYA AKSELERASI INTEGRASI ASESMEN FORMATIF DAN SUMATIF DALAM IMPLEMENTASI PENDEKATAN DEEP LEARNING DI PAUD - Bali, Engelbertus Nggalu; Muthmainah, Muthmainah; Lehan, Aflyyanti Dua; Nama Koten, Angelikus; Kale, Sartika (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
The purpose of this workshop was to enhance educators’ understanding and skills in designing and implementing assessment integrated with the principles and learning experiences of the deep learning approach in early childhood education (ECE). The workshop employed an andragogical approach, facilitated discussions, case studies, simulations, and hands-on practice grounded in local contexts. In this approach, assessment is positioned not merely as a measurement tool, but as an integral part of the child’s learning process. Participants included academics, supervisors, school principals, and ECE teachers. The results indicate that formative assessments (Assessment for Learning and Assessment as Learning) and summative assessment (Assessment of Learning) contextually support children's core learning experiences: understanding, applying, and reflecting. Assessment practices were carried out through systematic observation, portfolios, guided reflection, and project-based documentation. Findings highlight the importance of aligning assessment with meaningful, mindful, and joyful learning principles, and of cross-role collaboration in planning and implementation. This article recommends teacher training, the development of context-based assessment guidelines, the strengthening of professional learning communities, and the integration of digital support to promote reflective and child-centered assessment practices